WATER TEMPERATURE, HUMIDITY AND PH MEASURING DEVICE TO MAINTAIN PLANT GROWTH USING FUZZY LOGIC METHOD - Nelly Rachmawati; Jamaaluddin Jamaaluddin (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to develop an automatic plant watering system using fuzzy logic to maintain optimal plant growth conditions based on environmental factors. Method: The system was designed using an Arduino Uno microcontroller integrated with a DHT22 temperature sensor, soil moisture sensor, and water pH sensor to monitor environmental parameters. Fuzzy logic was applied to process temperature, soil moisture, and pH data to determine appropriate watering patterns automatically. The research involved two design stages: hardware design, including block diagrams and circuit layouts, and software design, represented through flowcharts explaining the system’s operational logic. Results: The developed prototype successfully demonstrated automatic control of plant watering, responding effectively to environmental changes and maintaining soil and water conditions suitable for plant growth. Novelty: This study introduces an intelligent, low-cost, and efficient irrigation system utilizing fuzzy logic, contributing to the advancement of smart agriculture by optimizing water usage and supporting sustainable plant care practices.